High density of TCF1+ stem-like tumor-infiltrating lymphocytes is associated with favorable disease-specific survival in NSCLC - Dagny Førde; Thomas Kilvær; Thomas Kilvær; Mona Irene Pedersen; Egil S Blix; Ilona Urbarova; Erna-Elise Paulsen; Erna-Elise Paulsen; Mehrdad Rakaee; Mehrdad Rakaee; Mehrdad Rakaee; Lill-Tove Rasmussen Busund; et al. (Frontiers in Immunology)
IntroductionTumor-infiltrating lymphocytes are both prognostic and predictive biomarkers for immunotherapy response. However, less is known about the survival benefits oftheir subpopulations.MethodsUsing machine learning models, we assessed the clinical association of the CD8+, PD1+, TCF1+ cel l subset by multiplex immunohistochemistry using tissue microarrays in 553 non-small cell lung cancer (NSCLC) patients and its correlation with other immune cell biomarkers.ResultsWe observed positive correlations between TCF1 and CD20 (r=0.37), CD3 (r=0.45)and CD4 (r=0.33). Notably, triple positive (CD8+PD1+TCF1+) were rare, only observed in 29 of 553 patients (5%). Our analysis revealed that cells coexpressing TCF1 with either CD8+ or PD1+ were independent prognostic markers of disease-specific survival in multivariable analysis (HR=0.728, p=0.029 for CD8+TCF1+, and HR=0.612, p=0.002 for PD1+TCF1+). To pilot the subtype of abundant CD8-TCF1+ cells, we explored an immune cell infiltrated whole slideimage and found the majority to be CD4+.DiscussionOverall, these findings suggest that assessment of CD8+, PD1+, TCF1+ could serve as a potential prognostic biomarker in NSCLC.